A gestão ambiental nas paisagens da bacia do Araripe no Estado do Ceará - Frederico de Holanda Bastos; Abner Monteiro Nunes Cordeiro; Francisco Edigley Macedo; Ruy Emmanuel Silva de Azevedo (Confins)
The Araripe basin is considered the largest sedimentary basin in northeastern Brazil, being extremely important for the state of Ceará, due to occupancy, which is directly linked to natural potential. Sedimentary deposits of this important geological unit possess great mineral potential and a huge fossil richness. Different uses of the natural resources can be found in the region, mainly agriculture, tourism, mining and urban expansion, which causes many environmental impacts and disturbance on natural dynamics. In this perspective, the government has taken some coercive actions, such as the establishment of protected areas and a complex system of environmental license procedures. However, these actions present severe structural issues, which limit the efficacy of environmental management. Thus, the present analysis focuses on a critical review of government actions towards environmental management in the Araripe basin landscapes at Ceará state.